The implementation of e-procurement "e-perolehan" factors in Sabah / Diana Dominic, Norlizuana Ali and R. M. Abdu Luqman R. M. Mohamed - Dominic, Diana; Ali, Norlizuana; R. M. Mohamed, R. M. Abdu Luqman (2017)
The importance of electronic procurement (e-procurement) is currently gaining momentum as it saves time and space. The same could be said regarding the studies that have been made, as large number of procurement articles have appeared in the literature in recent times. With the goal to fulfil the calls for more transparency in government procurement and as the government aims to implement paperless policy, e-procurement for the Government of Malaysia is known as e-perolehan. The main objective of this study is to identify the perceived problems, benefits, critical success factors and organisational performance regarding the implementation of e-perolehan. A theoretical framework has been adapted for the adoption of e-perolehan, and this subsequently has been tested with data collected from companies in Sabah. The results indicated that most business have a good perception of e-perolehan such as environmental issues, prompt payment, and better utilising their staff. Main problems are such as lack of skill and knowledge, immaturity of the technology and not being the top initiative or priority of the company. Critical success factors are the involvement of stakeholder and top management and accountability in business transaction and streamlines approval. The perceived organisational performance by utilising e-perolehan is that successful implementation could improve cost performance in their organisation. Thus, educating companies in both long and short-term benefits would encourage the application of e-perolehan.